(untitled) (Anclajes, 2024)
The correspondence of Carlo Cóccioli (1920-2003) traces the relationship among religiosity, male homosexuality, and urban sociability in the Mexican context, between 1954 and 1964. There are no publications on the impact that Cóccioli’s work had on Mexican homosexual people, yet there was a dense network of circulation of ideas related to Cóccioli’s denunciation of ecclesiastical hypocrisy and representation of homosexual love as a divine gift. The methodology consists of an interpretive reading that incorporates an analysis of significant historical and cultural frameworks to decipher the oblique meanings of these letters. Hence, the article demonstrated that there was a cultural current of resignification of Catholic symbology to celebrate homosexual experiences, and that the tension between pleasure and shame was one of the central axes in the experiences of homosexual men who were also believers. Well-off entendidos did not use a concept of pride centered on the visibility of their sexuality, rather they disdained the effeminacy and promiscuity of working-class jotos and vestidas but resorted to camp repertoires shared with these groups.